Survey of practices in relation to chronic pulmonary hypertension in neonates in the Canadian Neonatal Network and the National Institute of Child Health and Human Development Neonatal Research Network. (July 2020) - Baczynski, Michelle; Bell, Edward F.; Finan, Emer; McNamara, Patrick J.; Jain, Amish
Current knowledge gaps pertaining to diagnosis and management of neonatal chronic pulmonary hypertension (cPH) may result in significant variability in clinical practice. The objective of the study is to understand cPH management practices in neonatal intensive care units affiliated with the Canadian Neonatal Network (CNN) and National Institute of Child Health and Human Development Neonatal Research Network (NRN). A 32-question survey seeking practice details for cPH evaluation, diagnostic criteria, conservative measures, pharmacotherapeutics, and follow-up was e-mailed to a designated physician at each center. Responses were described as frequency (percentage) and compared between CNN and NRN, where appropriate. Overall response rate was 67% (CNN 20/28 (71%), NRN 9/15 (60%)). While 8 (28%) centers had standardized management protocols, 17 (59%) routinely evaluate high-risk patients; moderate-severe chronic lung disease being the commonest indication. While interventricular septal flattening on echocardiography was the commonest listed diagnostic criterion, several adjunctive indices were also identified. Asymptomatic neonates with cPH were managed expectantly (routine care) in 50% of sites, and using various conservative measures in others. Pulmonary vasodilators were prescribed for symptomatic cases, with 60% of sites using them early (86% reporting any use). Seventy-five percent of sites use inhaled nitric oxide and sildenafil citrate as first- and second-line agents, respectively. Use of standard protocols, cardiac catheterization, and conservative measures for asymptomatic cases was more common in NRN units ( p  < 0.05). While there is relative homogeneity in patient identification and diagnostic criteria used for neonatal cPH, significant interunit inconsistencies still exists in routine evaluation, use of additional investigations, management of asymptomatic cases, frequency and type of conservative measures, and choice of pulmonary vasodilators.